Impact of Jacobson’s Progressive Muscle Relaxation on Stress Levels of Exam Going MBBS Students of a Medical College in South Gujarat, India - Devashish Palkar; Sanjibani Panigrahi; Pooja Shatadal; Ritambhara Mehta (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Academic examinations are a very stressful event for an Bachelor of Medicine and Bachelor of Surgery (MBBS) student. While many students learn to deal with it through the use of helpful or unhelpful coping skills, many still end up with considerable psychological morbidity in the form of anxiety and depression along with deterioration in overall health. Jacobson’s Progressive Muscle Relaxation (JPMR) causes deep muscle relaxation. Aim: To find out the prevalence of stress and exam anxiety in students of 1st year MBBS and to study the impact of JPMR. Materials and Methods: It was a quasi-experimental, pretest and post-test interventional study conducted amongst the first year MBBS students studying at the Government Medical College Surat, Gujarat, India, during March to May 2019. Two months before their internal exams, 114 1st year MBBS students were recruited for the study. They were given a pretest proforma which comprised of socio-demographic profile, Perceived Stress Scale (PSS), Test Anxiety Scale (TAS) and General Health Questionnaire (GHQ) 28. They were asked to attend JPMR sessions over the following month in batches of 30 each and asked to practise JPMR for one month leading up to their exams. Total 43 students attended these sessions while 71 did not. After one month, all 114 students were again given a post-test proforma comprising of the same scales. Paired t-test was applied to compare the pretest and post-test scores to see the impact of JPMR. Results: The mean age of participants was 19 years.The students who completed their schooling in Gujarati medium and those who reported to be staying at hostel experienced significantly more TAS scores at baseline evaluation as compared to their counterparts from English medium schools and those staying at home respectively. There was a statistically significant reduction in mean scores of PSS and TAS before and after practice of JPMR in the 43 students who attended and practiced JPMR (p-value=0.005 and p-value=0.002, respectively; p-value <0.05 was considered to be significant). Conclusion: One month practice of JPMR was found to be effective in reduction of stress and exam anxiety.